Crosslinkable fluororubber composition and molded article

By using fluoroelastomer with high bromine or iodine content, a multifunctional crosslinking additive and specific metal compounds in the crosslinking fluoroelastomer composition, the problems of insufficient steam resistance and corrosion resistance of the crosslinking fluoroelastomer composition in the prior art under high temperature steam environment are solved, and molded products with excellent steam resistance and non-corrosion are achieved.

CN119585358APending Publication Date: 2025-03-07DAIKIN INDUSTRIES LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202380054297.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-07-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When used in high-temperature steam environments, the conventional crosslinked fluoroelastic compositions have insufficient steam resistance, resulting in the early reduction of the sealing performance of the sealing material and are prone to corrosion when in contact with the metal member.

Method used

A crosslinkable fluoroelastomer containing bromine atoms and/or iodine atoms, a multifunctional crosslinking additive, an organic peroxide, and a solid solution of magnesium oxide or alumina and magnesium oxide as the crosslinkable fluoroelastomer composition is used as the metal compound, and the content of the metal compound is controlled between 0.05 parts by mass to 0.50 parts by mass.

Benefits of technology

A molded product with excellent steam resistance is achieved, and it is not easy to corrode when in contact with a metal member, and extends the service life of the sealing material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245327800000171
    Figure BDA0005245327800000171
  • Figure BDA0005245327800000181
    Figure BDA0005245327800000181
  • Figure BDA0005245327800000191
    Figure BDA0005245327800000191
Patent Text Reader

Abstract

The present invention provides a crosslinkable fluororubber composition containing: a fluororubber containing bromine atoms and / or iodine atoms; a multifunctional crosslinking aid; an organic peroxide; and at least one metal compound selected from the group consisting of magnesium oxide and a solid solution of aluminum oxide and magnesium oxide, wherein the content of the metal compound is 0.05-0.50 parts by mass per 100 parts by mass of the fluororubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cross-linkable fluororubber composition and a molded product. Background Art

[0002] Patent document 1 describes a fluororubber-based sealing material composition, characterized in that it contains fluororubber and 2 parts by weight or more of a metal compound, 0.5 to 6 parts by weight of an organic peroxide, and 1 to 10 parts by weight of a multifunctional monomer relative to 100 parts by weight of the fluororubber, wherein the fluororubber has a fluorine content of 64% by weight or more, has a crosslinking site derived from a bromine-containing and / or iodine-containing compound, and is a copolymer capable of peroxide crosslinking, and the component units of the copolymer are as follows:

[0003] (a) 10 mol% to 25 mol% of perfluoromethoxymethoxyethyl vinyl ether component units;

[0004] (b) 60 mol% to 80 mol% of vinylidene fluoride component units;

[0005] (c) 5 mol% to 20 mol% of tetrafluoroethylene component units;

[0006] (d) 0 to 10 mol% of hexafluoropropylene component units; and

[0007] (e) A small amount of brominated and / or iodinated unsaturated fluorinated hydrocarbon component units serving as crosslinking sites (the total of (a) to (d) is taken as 100 mol %).

[0008] Patent Document 2 describes a vulcanizable fluororubber composition characterized by containing (a) a tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer, (b) an organic peroxide, (c) a co-crosslinking agent, and (d) hydrotalcite.

[0009] Patent Document 3 describes a fluororubber composition characterized in that it is prepared by mixing (a) a ternary fluororubber capable of being peroxide-cured, (b) a bituminous coal filler, (c) a hydrotalcite compound, (d) an organic peroxide, and (e) a co-crosslinking agent.

[0010] Patent Document 4 describes a fluororubber composition comprising 100 parts by weight of a peroxide-crosslinkable tetrafluoroethylene / vinylidene fluoride / hexafluoropropylene ternary copolymer rubber having a fluorine content of 64% by weight or more, (A) a specific surface area of ​​5 m 2 / g~20m 2 / g of carbon black 5 to 90 parts by weight, (B) asphaltene fine powder 5 to 40 parts by weight, (C) at least one of hydrophilicity-imparting talc 1 to 30 parts by weight and hydrophilicity-imparting clay 1 to 20 parts by weight, and (D) 0.5 to 6 parts by weight of an organic peroxide are used as a molding material for a fuel oil-based sealing material that comes into contact with fuel oil.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2004-217892

[0014] Patent Document 2: Japanese Patent Application Publication No. 2000-053835

[0015] Patent Document 3: International Publication No. 2006 / 006468

[0016] Patent Document 4: International Publication No. 2012 / 137724 Summary of the invention

[0017] Problems to be solved by the invention

[0018] An object of the present invention is to provide a cross-linkable fluororubber composition which can provide a molded article having excellent steam resistance and which is unlikely to corrode a metal member even when used in contact with the metal member.

[0019] Means for solving problems

[0020] According to the present invention, there is provided a cross-linkable fluororubber composition, which contains: a fluororubber containing bromine atoms and / or iodine atoms; a multifunctional cross-linking aid; an organic peroxide; and at least one metal compound selected from the group consisting of magnesium oxide and a solid solution of aluminum oxide and magnesium oxide, wherein the content of the above-mentioned metal compound is 0.05 to 0.50 parts by mass relative to 100 parts by mass of the above-mentioned fluororubber.

[0021] Effects of the Invention

[0022] According to the present invention, there is provided a cross-linkable fluororubber composition capable of obtaining a molded article having excellent steam resistance and which is less likely to corrode a metal member even when used in contact with the metal member. DETAILED DESCRIPTION

[0023] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0024] Patent Document 1 describes a fluororubber-based sealing material composition having a crosslinking site derived from a bromine-containing and / or iodine-containing compound, and containing a copolymer capable of being crosslinked by peroxide and a metal compound. In addition, calcium hydroxide and the like can be cited as the metal compound, and it is described that such a metal compound is usually used in an amount of 2 parts by weight or more, preferably 5 parts by weight to 15 parts by weight, relative to 100 parts by weight of the (uncrosslinked) fluororubber capable of being crosslinked by peroxide.

[0025] However, as taught in Patent Document 1, it is known that if the cross-linkable fluororubber composition contains a relatively large amount of metal compounds such as calcium hydroxide, the steam resistance of the molded product obtained from the cross-linkable fluororubber composition is insufficient. If the steam resistance of the molded product is insufficient, for example, when the molded product is used as a sealing material for sealing between metal components in a high-temperature steam environment, even if the corrosion of the metal components in contact with the molded product can be suppressed, the deterioration of the molded product itself cannot be suppressed, and there is a problem that the sealing performance of the molded product is reduced prematurely.

[0026] Therefore, in-depth research was conducted on means for solving this problem. As a result, it was found that by selecting magnesium oxide, or a solid solution of aluminum oxide and magnesium oxide as the metal compound and then using a small amount that could not be considered in the past common sense, surprisingly, a cross-linked fluororubber composition can be obtained, which can produce molded products with excellent steam resistance and, even when used in contact with metal components, can produce molded products that are not easy to corrode components.

[0027] That is, according to the present invention, there is provided a cross-linkable fluororubber composition, which contains: a fluororubber containing bromine atoms and / or iodine atoms; a multifunctional cross-linking aid; an organic peroxide; and at least one metal compound selected from the group consisting of magnesium oxide and a solid solution of aluminum oxide and magnesium oxide, wherein the content of the metal compound is 0.05 to 0.50 parts by mass relative to 100 parts by mass of the fluororubber.

[0028] Hereinafter, each component will be described in detail.

[0029] (Fluororubber)

[0030] The cross-linkable fluororubber composition of the present invention contains fluororubber. In the present invention, fluororubber refers to an amorphous fluoropolymer. "Amorphous" means that the size of the melting peak (ΔH) appearing in the differential scanning calorimetry [DSC] (heating temperature 10°C / min) or differential thermal analysis [DTA] (heating rate 10°C / min) of the fluoropolymer is 4.5 J / g or less. Fluororubber exhibits elastomeric properties by cross-linking. Elastomeric properties refer to the following properties: the polymer can be stretched and its original length can be maintained when the force required to stretch the polymer is no longer applied.

[0031] The fluororubber may be a partially fluorinated rubber or a perfluororubber.

[0032] In the present invention, the partially fluorinated rubber refers to a fluorinated polymer containing fluorinated monomer units and perfluorinated monomer units in an amount of less than 90 mol % relative to all polymerized units, and has a glass transition temperature of 20° C. or less and a melting peak (ΔH) of 4.5 J / g or less.

[0033] In the present invention, perfluoro rubber (perfluoroelastomer) refers to a fluorine-containing polymer in which the content of perfluoro monomer units relative to all polymerized units is 90 mol% or more, preferably 91 mol% or more, and has a glass transition temperature of 20°C or less and a melting peak (ΔH) of 4.5 J / g or less, and further, a polymer in which the concentration of fluorine atoms contained in the fluorine-containing polymer is 71 mass % or more, preferably 71.5 mass % or more. In the present invention, the concentration of fluorine atoms contained in the fluorine-containing polymer is calculated by the type and content of each monomer constituting the fluorine-containing polymer to obtain the concentration (mass %) of fluorine atoms contained in the fluorine-containing polymer.

[0034] In the present invention, a perfluoromonomer refers to a monomer that does not contain a carbon atom-hydrogen atom bond in the molecule. The above-mentioned perfluoromonomer may also be a monomer in which several fluorine atoms bonded to carbon atoms are replaced by chlorine atoms in addition to carbon atoms and fluorine atoms, or a monomer that has nitrogen atoms, oxygen atoms, sulfur atoms, phosphorus atoms, boron atoms or silicon atoms in addition to carbon atoms. As the above-mentioned perfluoromonomer, a monomer in which all hydrogen atoms are replaced by fluorine atoms is preferred. The above-mentioned perfluoromonomer does not contain a monomer that provides a crosslinking site.

[0035] The monomer providing a crosslinking site is a monomer having a crosslinking group (curing site monomer) which provides a crosslinking site for forming a crosslink with a crosslinking agent to the fluorine-containing polymer.

[0036] In the present invention, a fluororubber containing bromine atoms and / or iodine atoms is used. The fluororubber used in the present invention is a fluororubber containing bromine atoms and / or iodine atoms as crosslinking sites and is a fluororubber capable of being crosslinked by peroxide.

[0037] When the fluororubber contains iodine atoms, the iodine content is preferably 0.001 mass % to 10 mass %, more preferably 0.01 mass % or more, preferably 0.1 mass % or more, more preferably 5 mass % or less.

[0038] The fluororubber may be a partially fluorinated rubber or a perfluororubber. As a fluororubber, a molded product with better steam resistance can be obtained, which is also advantageous from the aspect of cost, so a partially fluorinated rubber is preferred, and a partially fluorinated rubber capable of peroxide crosslinking is more preferred.

[0039] As the partially fluorinated rubber, it is preferred to contain, for example, a compound selected from tetrafluoroethylene (TFE), vinylidene fluoride (VdF) and a compound of the general formula: CF2=CF-Rf a (Where Rf a -CF3 or -ORf b (Rf b The partially fluorinated rubber preferably contains a VdF unit or a TFE unit.

[0040] As the partially fluorinated rubber, there can be mentioned vinylidene fluoride (VdF) based fluororubber, tetrafluoroethylene (TFE) / propylene (Pr) based fluororubber, tetrafluoroethylene (TFE) / propylene / vinylidene fluoride (VdF) based fluororubber, ethylene / hexafluoropropylene (HFP) based fluororubber, ethylene / hexafluoropropylene (HFP) / vinylidene fluoride (VdF) based fluororubber, ethylene / hexafluoropropylene (HFP) / tetrafluoroethylene (TFE) based fluororubber, etc. Among them, at least one selected from the group consisting of vinylidene fluoride based fluororubber and tetrafluoroethylene / propylene based fluororubber is preferred.

[0041] As the fluororubber, from the perspective of being able to obtain a molded product with better steam resistance, it is preferably at least one selected from the group consisting of vinylidene fluoride-based fluororubber, tetrafluoroethylene / propylene-based fluororubber and perfluororubber, and more preferably at least one selected from the group consisting of vinylidene fluoride-based fluororubber and tetrafluoroethylene / propylene-based fluororubber.

[0042] As the vinylidene fluoride-based fluororubber, a copolymer composed of 45 mol % to 85 mol % of vinylidene fluoride and 55 mol % to 15 mol % of at least one other monomer copolymerizable with vinylidene fluoride is preferred, and a copolymer composed of 50 mol % to 80 mol % of vinylidene fluoride and 50 mol % to 20 mol % of at least one other monomer copolymerizable with vinylidene fluoride is more preferred.

[0043] Examples of at least one other monomer copolymerizable with vinylidene fluoride include tetrafluoroethylene [TFE], hexafluoropropylene [HFP], fluoroalkyl vinyl ether, chlorotrifluoroethylene [CTFE], trifluoroethylene, trifluoropropylene, pentafluoropropylene, trifluorobutylene, tetrafluoroisobutylene, hexafluoroisobutylene, vinyl fluoride, and the general formula (100): CHX 101 =CX 102 R 101 (Where X 101 and X 102 One of them is H and the other is F, Rf 101is a fluorinated monomer represented by a linear or branched fluoroalkyl group having 1 to 12 carbon atoms, general formula (170): CH2=CH-(CF2) n -X 171 (Where X 171 is H or F, n is an integer of 3 to 10), monomers such as monomers providing crosslinking sites, and non-fluorinated monomers such as ethylene, propylene, and alkyl vinyl ether. They can be used alone or in any combination.

[0044] As the fluoroalkyl vinyl ether, perfluoro(methyl vinyl ether) or perfluoro(propyl vinyl ether) is preferred, and perfluoro(methyl vinyl ether) is more preferred. These may be used alone or in any combination.

[0045] The fluorine-containing monomer represented by the general formula (100) is preferably 2,3,3,3-tetrafluoropropylene or 1,3,3,3-tetrafluoropropylene, and more preferably 2,3,3,3-tetrafluoropropylene.

[0046] The at least one other monomer copolymerizable with vinylidene fluoride is preferably at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether, CTFE and a fluorinated monomer represented by the general formula (100), and more preferably at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether and 2,3,3,3-tetrafluoropropylene.

[0047] Specific examples of vinylidene fluoride-based fluororubbers include VdF / HFP-based rubbers, VdF / HFP / TFE-based rubbers, VdF / CTFE-based rubbers, VdF / CTFE / TFE-based rubbers, VdF / fluorinated monomer-based rubbers represented by the general formula (100), VdF / fluorinated monomer-based rubbers represented by the general formula (100) / TFE-based rubbers, VdF / perfluoro(methyl vinyl ether) [PMVE]-based rubbers, VdF / PMVE / TFE-based rubbers, and VdF / PMVE / TFE / HFP-based rubbers. Among these, at least one copolymer selected from the group consisting of VdF / HFP-based rubbers, VdF / HFP / TFE-based rubbers, and VdF / 2,3,3,3-tetrafluoropropylene-based rubbers is preferred.

[0048] As the VdF / HFP-based rubber, the molar ratio of VdF / HFP is preferably 45 to 85 / 55 to 15, more preferably 50 to 80 / 50 to 20, and even more preferably 60 to 80 / 40 to 20.

[0049] As the VdF / HFP / TFE-based rubber, the molar ratio of VdF / HFP / TFE is preferably 40 to 80 / 10 to 35 / 10 to 35.

[0050] As the VdF / 2,3,3,3-tetrafluoropropylene rubber, the molar ratio of VdF / 2,3,3,3-tetrafluoropropylene is preferably 45 to 85 / 55 to 15, more preferably 50 to 80 / 50 to 20, and even more preferably 60 to 80 / 40 to 20.

[0051] The tetrafluoroethylene / propylene fluororubber is preferably a copolymer composed of 45 mol% to 70 mol% of tetrafluoroethylene, 55 mol% to 30 mol% of propylene, and 0 to 5 mol% of a fluorine-containing monomer providing a crosslinking site.

[0052] The perfluororubber is preferably a perfluororubber containing TFE, for example, at least one selected from the group consisting of a copolymer of TFE / a fluorinated monomer represented by the general formula (11), (12) or (13) and a copolymer of TFE / a fluorinated monomer represented by the general formula (11), (12) or (13) / a monomer providing a crosslinking site.

[0053] Preferred general formula (11): CF2=CF-ORf 111

[0054] (Where Rf 111 represents a fluorinated monomer represented by a perfluoroalkyl group having 1 to 10 carbon atoms. 111 A perfluoroalkyl group having 1 to 5 carbon atoms is preferred.

[0055] General formula (12): CF2=CFOCF2ORf 121

[0056] (Where Rf 121 A fluorinated monomer represented by a linear or branched perfluoroalkyl group having 1 to 6 carbon atoms, a cyclic perfluoroalkyl group having 5 to 6 carbon atoms, or a linear or branched perfluorooxyalkyl group having 2 to 6 carbon atoms and containing 1 to 3 oxygen atoms

[0057] General formula (13): CF2=CFO(CF2CF(Y 131 )O) m (CF2) n F

[0058] (Where Y 131 represents a fluorine atom or a trifluoromethyl group. m is an integer from 1 to 4. n is an integer from 1 to 4. ) represents a fluorine-containing monomer

[0059] The fluorinated monomer represented by the general formula (11) is preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether), and more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether) and perfluoro(propyl vinyl ether).

[0060] The fluorine-containing monomer represented by the general formula (12) is preferably at least one selected from the group consisting of CF2=CFOCF2OCF3, CF2=CFOCF2OCF2CF3 and CF2=CFOCF2OCF2CF2OCF3.

[0061] The fluorinated monomer represented by the general formula (13) is preferably at least one selected from the group consisting of CF2=CFOCF2CF(CF3)O(CF2)3F, CF2=CFO(CF2CF(CF3)O)2(CF2)3F and CF2=CFO(CF2CF(CF3)O)2(CF2)2F.

[0062] The composition of the TFE / PMVE copolymer is preferably 45 to 90 / 10 to 55 (mol %), more preferably 55 to 80 / 20 to 45, and further preferably 55 to 70 / 30 to 45.

[0063] The copolymer composition of TFE / PMVE / crosslinking site providing monomer is preferably 45 to 89.9 / 10 to 54.9 / 0.01 to 4 (mol %), more preferably 55 to 77.9 / 20 to 49.9 / 0.1 to 3.5, and further preferably 55 to 69.8 / 30 to 44.8 / 0.2 to 3.

[0064] The composition of the copolymer of TFE / fluorinated monomer represented by the general formula (11), (12) or (13) having 4 to 12 carbon atoms is preferably 50 to 90 / 10 to 50 (mol %), more preferably 60 to 88 / 12 to 40, further preferably 65 to 85 / 15 to 35.

[0065] The copolymer composition of TFE / fluorinated monomer represented by the general formula (11), (12) or (13) having 4 to 12 carbon atoms / monomer providing a crosslinking site is preferably 50 to 89.9 / 10 to 49.9 / 0.01 to 4 (mol %), more preferably 60 to 87.9 / 12 to 39.9 / 0.1 to 3.5, and still more preferably 65 to 84.8 / 15 to 34.8 / 0.2 to 3.

[0066] Outside these composition ranges, the properties as a rubber elastic body are lost and properties close to those of a resin tend to be exhibited.

[0067] The perfluororubber is preferably at least one selected from the group consisting of a copolymer of TFE / fluorinated monomer represented by the general formula (13) / fluorinated monomer providing a crosslinking site, a copolymer of TFE / perfluorovinyl ether represented by the general formula (13), a copolymer of TFE / fluorinated monomer represented by the general formula (11), and a copolymer of TFE / fluorinated monomer represented by the general formula (11) / monomer providing a crosslinking site.

[0068] Examples of the perfluororubber include perfluororubbers described in International Publication No. 97 / 24381, Japanese Examined Patent Publication No. 61-57324, Japanese Examined Patent Publication No. 4-8118, Japanese Examined Patent Publication No. 5-13961, and the like.

[0069] Fluororubber is also preferably composed of a copolymer containing polymerization units from monomers providing crosslinking sites. As monomers providing crosslinking sites, for example, iodine-containing monomers such as perfluoro(6,6-dihydro-6-iodo-3-oxa-1-hexene) and perfluoro(5-iodo-3-oxa-1-pentene) described in Japanese Patent Publication No. 5-63482 and Japanese Patent Publication No. 7-316234, bromine-containing monomers described in Japanese Patent Publication No. 4-505341, cyano-containing monomers, carboxyl-containing monomers, and alkoxycarbonyl-containing monomers described in Japanese Patent Publication No. 4-505345 and Japanese Patent Publication No. 5-500070 can be cited.

[0070] Fluororubber is preferably obtained by using a chain transfer agent during polymerization. As the above-mentioned chain transfer agent, a bromine compound or an iodine compound can be used. As a polymerization method using a bromine compound or an iodine compound, for example, the following method can be cited: in a substantially oxygen-free state, in the presence of a bromine compound or an iodine compound, emulsion polymerization is carried out in an aqueous medium while applying pressure (iodine transfer polymerization method). As a representative example of the bromine compound or iodine compound used, for example, the general formula can be cited:

[0071] R 2 I x Br y

[0072] (where x and y are integers from 0 to 2 and satisfy 1≤x+y≤2, R 2 A compound represented by a saturated or unsaturated fluorinated hydrocarbon group or chlorofluorocarbon group having 1 to 16 carbon atoms, or a hydrocarbon group having 1 to 3 carbon atoms, which may contain an oxygen atom). By using a bromine compound or an iodine compound, iodine or bromine is introduced into the polymer to function as a crosslinking point.

[0073] From the perspective of obtaining a molded product with better steam resistance and less prone to further corrosion of metal components, the fluorine content of the fluororubber is preferably 55% to 73% by mass, more preferably 61% by mass or more, further preferably 63% by mass or more, further preferably 65% ​​by mass or more, particularly preferably 67% by mass or more, most preferably 69% by mass or more, and more preferably less than 71% by mass. The fluorine content of the fluororubber can be determined by 19 The composition of the fluororubber measured by F-NMR was determined by calculation.

[0074] The Mooney viscosity (ML1+10(100°C)) of the fluororubber at 100°C is preferably 2 or more, more preferably 5 or more, and even more preferably 10 or more. It is preferably 200 or less, more preferably 120 or less, even more preferably 100 or less, and particularly preferably 80 or less. The Mooney viscosity is a value measured in accordance with ASTM-D1646-15 and JIS K6300-1:2013.

[0075] (Metal Compounds)

[0076] In the present invention, as metallic compound, use at least one selected from the group consisting of the solid solution of magnesium oxide and aluminum oxide and magnesium oxide. If metallic compounds other than these, for example metallic compounds such as calcium hydroxide, hydrotalcite, then can not obtain the excellent molded product of steam resistance, or can not obtain the excellent molded product of compression set characteristic. Known magnesium oxide has hygroscopicity in the same manner as calcium hydroxide. It is unpredictable by such technical common sense, but it is clear that by using magnesium oxide and the solid solution containing magnesium oxide, the excellent molded product of steam resistance can be obtained.

[0077] In addition, in the present invention, the content of at least one selected from the group consisting of magnesium oxide and a solid solution of aluminum oxide and magnesium oxide is within the range of 0.05 to 0.50 parts by mass relative to 100 parts by mass of fluororubber. Even when magnesium oxide and a solid solution of aluminum oxide and magnesium oxide are used as metal compounds, the desired effect cannot be obtained if the content is outside the above numerical range. If the content of the metal compound in the cross-linkable fluororubber composition is too small, it is difficult to obtain a molded product with a metal component that is not easily corroded. If the content of the metal compound in the cross-linkable fluororubber composition is too much, it is difficult to obtain a molded product with excellent steam resistance, and sometimes the compression set of the obtained molded product becomes too large.

[0078] From the perspective of obtaining a molded product having better steam resistance and being less likely to cause corrosion to metal components, the content of the metal compound in the cross-linkable fluororubber composition is preferably 0.40 part by mass or less, more preferably 0.30 part by mass or less, further preferably 0.20 part by mass or less, further preferably 0.15 part by mass or less, and particularly preferably 0.11 part by mass or less, relative to 100 parts by mass of the fluororubber.

[0079] When the crosslinkable fluororubber composition contains magnesium oxide as a metal compound, from the aspect of obtaining a molded product with more excellent steam resistance and less likely to corrode metal components, the content of magnesium oxide is preferably 0.06 parts by mass or more, more preferably 0.07 parts by mass or more, further preferably 0.08 parts by mass or more, still more preferably 0.09 parts by mass or more, preferably 0.40 parts by mass or less, more preferably 0.30 parts by mass or less, further preferably 0.20 parts by mass or less, still more preferably 0.15 parts by mass or less, and particularly preferably 0.11 parts by mass or less, based on 100 parts by mass of the fluororubber.

[0080] When the crosslinkable fluororubber composition contains a solid solution as a metal compound, from the aspect of obtaining a molded product with more excellent steam resistance and less likely to corrode metal components, the content of the solid solution is preferably 0.40 parts by mass or less, more preferably 0.30 parts by mass or less, further preferably 0.20 parts by mass or less, still more preferably 0.15 parts by mass or less, and particularly preferably 0.11 parts by mass or less, based on 100 parts by mass of the fluororubber.

[0081] The solid solution of alumina and magnesium oxide can have, for example, the following formula:

[0082] (Mg 1-x Al x )O 1+0.5x

[0083] (In the formula, 0 < x < 0.4.) The chemical composition shown.

[0084] The solid solution of alumina and magnesium oxide can have, for example, Mg 0.7 Al 0.3 O 1.15 The chemical composition shown.

[0085] The solid solution is generally distinguished from the hydrotalcite compound containing anions in terms of not containing anions.

[0086] The content of alumina (Al2O3) in the solid solution is, for example, 10% to 40% by mass based on the mass of the solid solution. In addition, the content of magnesium oxide (MgO) in the solid solution is, for example, 90% to 60% by mass based on the mass of the solid solution.

[0087] (Crosslinking agent)

[0088] In the present invention, an organic peroxide is used as the crosslinking agent.

[0089] The organic peroxide is not particularly limited as long as it is a crosslinking agent generally used in peroxide crosslinking, and may be an organic peroxide that easily generates peroxide radicals in the presence of heat or a redox system. Specifically, 1,1-bis(tert-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroperoxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α'-bis(tert-butylperoxy)-p-diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, benzoyl peroxide, tert-butylbenzene peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butylperoxymaleate, tert-butylperoxyisopropylcarbonate, tert-butylperoxybenzoate, and the like may be cited. Among these, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne are preferred.

[0090] The content of the organic peroxide is preferably 0.05 to 10 parts by mass, more preferably 1.0 to 5 parts by mass, based on 100 parts by mass of the fluororubber.

[0091] (Multifunctional cross-linking aid)

[0092] The cross-linkable fluororubber composition of the present invention further contains a polyfunctional cross-linking aid.

[0093] Examples of the multifunctional crosslinking aid include triallyl cyanurate, trimethylallyl isocyanurate, triallyl isocyanurate (TAIC), 1,3,5-triacryloyl hexahydro-s-triazine, triallyl trimellitate, N,N'-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalamide, triallyl phosphate, bismaleimide, fluorinated triallyl isocyanurate (1,3,5-tris(2,3,3-trifluoro-2-propenyl) -1,3,5-triazine-2,4,6-trione), tri(diallylamine)-s-triazine, triallyl phosphite, N,N-diallylacrylamide, 1,6-divinyldodecafluorohexane, hexaallylphosphoramide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylmalonamide, trivinyl isocyanurate, 2,4,6-trivinylmethyltrisiloxane, tri(5-norbornene-2-methylene)cyanurate, triallyl phosphite, etc. As a multifunctional crosslinking aid, a compound having 2 to 4 unsaturated functional groups and a nitrogen-containing heterocyclic ring is preferred, and at least one selected from the group consisting of triallyl isocyanurate and trimethylallyl isocyanurate is more preferred, and triallyl isocyanurate (TAIC) is further preferred. When kneading the fluororubber and the polyfunctional crosslinking aid, a material obtained by impregnating an inert inorganic powder or the like with the polyfunctional crosslinking aid may be used.

[0094] The content of the polyfunctional crosslinking aid is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the fluororubber.

[0095] (Other ingredients)

[0096] The crosslinkable fluororubber composition of the present invention may or may not contain an acid acceptor within a range that does not impair the desired effect exerted by the crosslinkable fluororubber composition of the present invention. Examples of the acid acceptor include metal oxides such as calcium oxide, hydrotalcite, bismuth oxide, zinc oxide, metal hydroxides such as calcium hydroxide, alkali metal silicates such as sodium metasilicate recorded in JP-A-2011-522921, and metal salts of weak acids recorded in JP-A-2003-277563. Examples of metal salts of weak acids include carbonates, benzoates, oxalates, and phosphites of Ca, Sr, Ba, Na, and K.

[0097] The acid acceptor is preferably at least one selected from the group consisting of metal oxides (excluding magnesium oxide and a solid solution of aluminum oxide and magnesium oxide), metal hydroxides, alkali metal silicates, hydrotalcites, and metal salts of weak acids.

[0098] In one embodiment of the cross-linkable fluororubber composition of the present invention, at least one metal compound selected from the group consisting of alkali metals, alkali metal oxides, alkali metal hydroxides, alkali metal salts, alkaline earth metals, alkaline earth metal oxides, alkaline earth metal hydroxides and alkaline earth metal salts (excluding magnesium oxide and a solid solution of aluminum oxide and magnesium oxide) is contained or not contained, and the content of the above metal compound is 0 to 1 part by mass relative to 100 parts by mass of fluororubber. When the cross-linkable fluororubber composition of the present invention has such a structure, there is a tendency that the steam resistance of the obtained molded product is further improved. The content of the above metal compound is preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, and particularly preferably not contained.

[0099] In one embodiment of the cross-linkable fluororubber composition of the present invention, an acid acceptor such as calcium hydroxide, magnesium oxide, or hydrotalcite (excluding magnesium oxide and a solid solution of aluminum oxide and magnesium oxide) may or may not be contained, and the content of the acid acceptor is 0 to 1 part by mass relative to 100 parts by mass of the fluororubber. When the cross-linkable fluororubber composition of the present invention has such a structure, there is a tendency that the steam resistance of the obtained molded article is further improved. The content of the acid acceptor (excluding magnesium oxide and a solid solution of aluminum oxide and magnesium oxide) is preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, and particularly preferably not contained.

[0100] The cross-linkable fluororubber composition of the present invention may be mixed with various additives such as conventional additives mixed in cross-linkable fluororubber compositions, such as fillers (carbon black, bituminous coal, barium sulfate, diatomaceous earth, calcined clay, talc, etc.), processing aids (wax, etc.), plasticizers, colorants, stabilizers, adhesion-imparting agents (coumarone resin, coumarone-indene resin, etc.), mold release agents, conductivity-imparting agents, thermal conductivity-imparting agents, surface non-adhesives, flexibility-imparting agents, heat resistance-improving agents, flame retardants, foaming agents, and antioxidants described in International Publication No. 2012 / 023485, as needed. It may also be mixed with one or more conventional cross-linking agents and cross-linking accelerators different from the above.

[0101] As fillers, there can be mentioned metal oxides such as titanium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide and aluminum hydroxide; carbonates such as magnesium carbonate, aluminum carbonate, calcium carbonate, and barium carbonate; silicates such as magnesium silicate, calcium silicate, and aluminum silicate; sulfates such as aluminum sulfate, calcium sulfate, and barium sulfate; metal sulfides such as molybdenum disulfide, iron sulfide, and copper sulfide; diatomaceous earth, asbestos, zinc barium white (zinc sulfide / barium sulfide), graphite, carbon fluoride, calcium fluoride, coke, quartz powder, talc, mica powder, wollastonite, carbon fiber, aramid fiber, various whiskers, glass fiber, organic reinforcing agent, organic filler, polytetrafluoroethylene, fluorine-containing thermoplastic resin, mica, silica, diatomaceous earth, clay, etc.

[0102] The content of fillers such as carbon black is not particularly limited, but is preferably 0 to 300 parts by mass, more preferably 1 to 150 parts by mass, further preferably 2 to 100 parts by mass, and particularly preferably 2 to 75 parts by mass, based on 100 parts by mass of the fluororubber.

[0103] The content of processing aids such as wax is preferably 0 to 10 parts by mass, more preferably 0 to 5 parts by mass, relative to 100 parts by mass of fluororubber. If processing aids, plasticizers, and mold release agents are used, the mechanical properties and sealing properties of the resulting molded product tend to be reduced, so these contents need to be adjusted within the range allowed by the properties of the target molded product.

[0104] The cross-linkable fluororubber composition of the present invention may contain a dialkyl sulfone compound. Examples of the dialkyl sulfone compound include dimethyl sulfone, diethyl sulfone, dibutyl sulfone, methyl ethyl sulfone, diphenyl sulfone, cyclopentane sulfone, and the like. The content of the dialkyl sulfone compound is preferably 0 to 10 parts by mass, more preferably 0 to 5 parts by mass, and particularly preferably 0 to 3 parts by mass relative to 100 parts by mass of the fluororubber. In the case where the cross-linkable fluororubber composition of the present invention contains a dialkyl sulfone compound, the lower limit of the content of the dialkyl sulfone compound may be, for example, 0.1 parts by mass or more relative to 100 parts by mass of the fluororubber.

[0105] The crosslinkable fluororubber composition of the present invention is obtained by kneading fluororubber, metal compound, organic peroxide, multifunctional crosslinking aid, filler, etc. using a commonly used rubber kneading device. As the rubber kneading device, a roll, a kneader, a Banbury mixer, a closed mixer, a twin-screw extruder, etc. can be used.

[0106] The cross-linkable fluororubber composition of the present invention can be suitably used to obtain a molded article that comes into contact with one or both of steam and hot water. Therefore, the present invention relates to a cross-linkable fluororubber composition for forming a molded article that comes into contact with one or both of steam and hot water, and more specifically, to the use of the cross-linkable fluororubber composition for obtaining a molded article that suppresses volume change when in contact with one or both of steam and hot water.

[0107] (Molding products)

[0108] By crosslinking the crosslinkable fluororubber composition of the present invention, a molded article can be obtained.

[0109] As a method for crosslinking the crosslinkable fluororubber composition of the present invention, it is needless to say that commonly used methods such as pressure crosslinking, steam crosslinking, and oven crosslinking can be used. The crosslinking reaction can be carried out under any conditions, such as normal pressure, pressure, reduced pressure, and in the air. The crosslinking conditions can be appropriately determined according to the type of crosslinking agent used, and are usually heated at a temperature of 150°C to 300°C for 1 minute to 24 hours. In the case of pressure crosslinking and steam crosslinking, it is preferably carried out at a temperature of 150°C to 180°C. As for the crosslinking time, it is sufficient to carry out at least until the crosslinking time T90, for example, 1 minute to 2 hours. In the case of subsequent oven crosslinking (after pressure crosslinking or steam crosslinking), it is preferably carried out at a temperature of 170°C to 250°C, but it is not necessarily required. The crosslinking time of oven crosslinking is preferably 0 to 48 hours, for example.

[0110] The crosslinkable fluororubber composition of the present invention can also be molded into a molded article. The molding can be performed by a conventionally known method, for example, compression molding, injection molding, extrusion molding, calendar molding, etc.

[0111] Examples of the use form of the molded product include various sealing materials or gaskets such as rings, gaskets, washers, diaphragms, oil seals, bearing seals, lip seals, plunger seals, door seals, lip and end seals, gas transport plate seals, wafer support seals, and barrel seals. As a sealing material, it can be used for applications requiring heat resistance, solvent resistance, chemical resistance, and non-adhesiveness.

[0112] In addition, the molded products can also be used as pipes, hoses, rollers, various rubber rollers, flexible joints, rubber sheets, coatings, belts, shock absorbers, valves, valve seats, valve bodies, chemical-resistant coating materials, laminating materials, lining materials, etc.

[0113] The cross-sectional shapes of the above-mentioned rings, gaskets and seals can be various shapes, specifically, they can be square, O-shaped, ring-shaped, etc., or they can be D-shaped, L-shaped, T-shaped, V-shaped, X-shaped, Y-shaped and other special shapes.

[0114] In particular, the molded article obtained by molding the cross-linkable fluororubber composition of the present invention has excellent steam resistance and is unlikely to corrode the metal member even when used in contact with the metal member. Therefore, it can be suitably used as a molded article that comes into contact with one or both of steam and hot water.

[0115] In one embodiment of the molded article of the present invention, the molded article has a contact surface that contacts one or both of steam and hot water, and at least the contact surface is composed of a molded article obtained by crosslinking a crosslinkable fluororubber composition. That is, the molded article obtained from the crosslinkable fluororubber composition can be used to form at least the contact surface with one or both of steam and hot water in the molded article that contacts one or both of steam and hot water.

[0116] The molded articles that come into contact with one or both of steam and hot water include molded articles (such as containers, hoses, seals, gaskets, etc.) that may come into contact with one or both of steam and hot water in standard use. Examples of these molded articles include molded articles (such as containers, hoses, seals, gaskets, etc.) used in boilers, turbines, steam cleaning machines, hot water cleaning machines, etc.

[0117] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0118] <1> According to a first aspect of the present invention, there is provided a cross-linkable fluororubber composition comprising:

[0119] Fluororubber containing bromine atoms and / or iodine atoms;

[0120] Multifunctional cross-linking aid;

[0121] Organic peroxides; and

[0122] at least one metal compound selected from the group consisting of magnesium oxide and a solid solution of aluminum oxide and magnesium oxide,

[0123] The content of the metal compound is 0.05 to 0.50 parts by mass based on 100 parts by mass of the fluororubber.

[0124] <2> According to a second aspect of the present invention, there is provided a cross-linkable fluororubber composition according to the first aspect, wherein the fluororubber is at least one selected from the group consisting of vinylidene fluoride-based fluororubber, tetrafluoroethylene / propylene-based fluororubber and perfluororubber.

[0125] <3> According to a third aspect of the present invention, there is provided the cross-linkable fluororubber composition according to the first aspect or the second aspect, wherein the content of the organic peroxide is 0.05 to 10 parts by mass based on 100 parts by mass of the fluororubber.

[0126] <4> According to a fourth aspect of the present invention, there is provided a cross-linkable fluororubber composition according to any one of the first to third aspects, wherein the content of the polyfunctional cross-linking aid is 0.1 to 10 parts by mass based on 100 parts by mass of the fluororubber.

[0127] <5> According to a fifth aspect of the present invention, there is provided a molded article obtained by crosslinking the crosslinkable fluororubber composition according to any one of the first to fourth aspects.

[0128] Example

[0129] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to the examples.

[0130] Each numerical value in the examples was measured by the following method.

[0131] <Monomer composition of fluororubber>

[0132] use 19 The measurement was performed by F-NMR (AC300P model manufactured by Bruker).

[0133] <Iodine content>

[0134] Na2CO3 and K2CO3 are mixed in a ratio of 1 to 1 (weight ratio), and the obtained mixture is dissolved in 20 ml of pure water to prepare an absorption liquid. 5 mg Na2SO3 is mixed in 12 mg of a sample (fluororubber) and a mixture is prepared, and it is burned in oxygen in a quartz flask, and the generated combustion gas is introduced into the absorption liquid. After the obtained absorption liquid is placed for 30 minutes, the concentration of iodine ions in the absorption liquid is measured using Shimadzu 20A ion chromatography. The calibration curve made using a KI standard solution containing 0.5 ppm of iodine ions and a KI standard solution containing 1.0 ppm is used to determine the content of iodine ions.

[0135] <Mooney viscosity>

[0136] The measurement was performed in accordance with ASTM D1646-15 and JIS K6300-1: 2013. The measurement temperature was 100°C.

[0137] <Heat of Fusion>

[0138] Using a differential scanning calorimeter (DSC822e manufactured by Mettler Toredo or X-DSC7000 manufactured by Hitachi High-Tech Science), 10 mg of a sample was heated at 20°C / min to obtain a DSC curve, and the heat of fusion was calculated from the magnitude of the melting peak (ΔH) appearing in the DSC curve.

[0139] <100% modulus, tensile strength and elongation at break>

[0140] A test piece in the shape of dumbbell No. 6 was prepared using a crosslinked sheet having a thickness of 2 mm. Using the obtained test piece and a tensile tester (Tensilon RTG-1310 manufactured by A&D Co.), 100% modulus (M100), tensile strength (TB) and elongation at break (EB) at 23° C. were measured at 500 mm / min in accordance with JIS K6251:2010.

[0141] <Shore Hardness (HS)>

[0142] Three crosslinked sheets each having a thickness of 2 mm were stacked and used, and the hardness (peak value) was measured using a type A durometer in accordance with JIS K6253-3:2012.

[0143] <Compression Set (CS)>

[0144] The compression set was measured using a small test piece for compression set measurement (P-24, O-ring) in accordance with Method A of JIS K6262:2013 at a compression rate of 25%, a test temperature of 200° C., and a test time of 70 hours.

[0145] <Corrosion test>

[0146] A cross-linked sheet with a thickness of 2 mm was sandwiched between two metal plates made of SUS304, and pressure was applied from both sides to compress the cross-linked sheet at a compression rate of 10%, and the sheet was placed in a steam vulcanizer in this state. In the steam vulcanizer, the metal plate sandwiching the cross-linked sheet was exposed to steam under the conditions of 170°C, 6.9 MPa, and 70 hours. The metal plate sandwiching the cross-linked sheet was taken out of the steam vulcanizer. The surface of the metal plate where the metal plate and the cross-linked sheet were in close contact was visually observed and evaluated according to the following criteria.

[0147] (Corrosion Evaluation)

[0148] Poorly tarnished.

[0149] Acceptable Although gloss remained, discoloration was observed in many parts.

[0150] Good: Although gloss remained, discoloration was observed in a small amount.

[0151] Excellent glossiness remains and no discoloration is observed.

[0152] <Steam resistance>

[0153] A cross-linked sheet with a length of 20 mm, a width of 20 mm, and a thickness of 2 mm was placed in a steam vulcanizer. In the steam vulcanizer, the cross-linked sheet was exposed to steam at 170° C., 6.9 MPa, and 70 hours. The cross-linked sheet was taken out of the steam vulcanizer, and the 100% modulus (M100), tensile strength (TB), elongation at break (EB), and Shore hardness (HS) at 23° C. were measured by the above method.

[0154] In addition, the specific gravity and mass of the crosslinked sheet before and after exposure to steam were measured, and the volume change rate was calculated according to the following formula: The specific gravity was measured using an automatic densimeter DMA-220H (manufactured by Shinko Electric Co., Ltd.).

[0155] Volume change rate (%) = {[(mass of the cross-linked sheet after immersion) / (specific gravity of the cross-linked sheet after immersion)] - [(mass of the cross-linked sheet before immersion) / (specific gravity of the cross-linked sheet before immersion)]} / [(mass of the cross-linked sheet before immersion)] / (specific gravity of the cross-linked sheet before immersion)] × 100

[0156] In Examples and Comparative Examples, the following materials were used.

[0157] Fluororubber A

[0158] Vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene copolymer

[0159] Vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene: 50 / 20 / 30 (molar ratio)

[0160] Iodine content: 0.25 mass%

[0161] Mooney viscosity (ML1+10(100℃)): 50

[0162] Heat of fusion: Not confirmed in the second round

[0163] Fluororubber B

[0164] Vinylidene fluoride / tetrafluoroethylene / perfluoro(methyl vinyl ether) copolymer

[0165] Vinylidene fluoride / tetrafluoroethylene / perfluoro(methyl vinyl ether): 75 / 7 / 18 (molar ratio)

[0166] Iodine content: 0.32 mass%

[0167] Mooney viscosity (ML1+10(100℃)): 68

[0168] Heat of fusion: Not confirmed in the second round

[0169] Fluororubber C

[0170] Tetrafluoroethylene / perfluoro(methyl vinyl ether) copolymer

[0171] Tetrafluoroethylene / perfluoro(methyl vinyl ether): 62.5 / 37.5 (molar ratio)

[0172] Iodine content: 0.55 mass%

[0173] Mooney viscosity (ML1+10(100℃)): 65

[0174] Heat of fusion: Not confirmed in the second round

[0175] Carbon black: MT carbon (N2SA = 8m 2 / g, DBP oil absorption = 43ml / 100g)

[0176] Multifunctional crosslinking aid: triallyl isocyanurate

[0177] Organic peroxide: 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane

[0178] Additive-A: Calcium hydroxide (NICC5000 manufactured by Inoue Lime Industry Co., Ltd.)

[0179] Additive-B: Hydrotalcite (DHT-4A manufactured by Kyowa Chemical Industry Co., Ltd.)

[0180] Additive-C: magnesium oxide (Kyowamag 150 manufactured by Kyowa Chemical Industry Co., Ltd.)

[0181] Additive-D: Solid solution of aluminum oxide and magnesium oxide (KW-2200 manufactured by Kyowa Chemical Industry Co., Ltd.) (MgO / Al2O3=59.5 / 34.5 (mass ratio))

[0182] Comparative Examples 1 to 6 and Examples 1 to 21

[0183] The components were mixed according to the formula in Table 1 and kneaded on an open roll to prepare a crosslinkable fluororubber composition. The crosslinkable fluororubber composition was pressed at 160°C for 30 minutes to crosslink it, and then heated in an oven at 180°C for 4 hours to obtain a crosslinked sheet (thickness 2 mm). The evaluation results of the obtained crosslinked sheet are shown in Tables 1 to 3.

[0184]

[0185]

[0186]

[0187]

Claims

1. A cross-linkable fluororubber composition comprising: Fluororubber containing bromine atoms and / or iodine atoms; Multifunctional cross-linking aid; Organic peroxides; as well as at least one metal compound selected from the group consisting of magnesium oxide and a solid solution of aluminum oxide and magnesium oxide, The content of the metal compound is 0.05 to 0.50 parts by mass based on 100 parts by mass of the fluororubber.

2. The cross-linkable fluororubber composition according to claim 1, wherein The fluororubber is at least one selected from the group consisting of vinylidene fluoride-based fluororubber, tetrafluoroethylene / propylene-based fluororubber, and perfluororubber.

3. The cross-linkable fluororubber composition according to claim 1 or 2, wherein The content of the organic peroxide is 0.05 parts by mass to 10 parts by mass based on 100 parts by mass of the fluororubber.

4. The cross-linkable fluororubber composition according to any one of claims 1 to 3, wherein The content of the multifunctional cross-linking aid is 0.1 parts by mass to 10 parts by mass based on 100 parts by mass of the fluororubber.

5. A molded article obtained by crosslinking the crosslinkable fluororubber composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Manufacture of fluorine-containing elastic copolymer

    JP1986057324B2

  • Apparatus for filtering and activating water or bath water

    JP1992008118B2

  • Iodine cure sites having a bromo-production of perfluoropolymer

    JP1992505341A

  • Production of a perfluoropolymer having iodine cure sites containing cyano

    JP1992505345A

  • Emulsion polymerization of fluoroelastomer

    JP1993013961B2